Chronical kidney disease in clinical practice: non progredi est regredi (lat. not to go forward is to go back) - A. L. Vertkin; N. A. Burakova; Yu. V. Sedyakina; S. S. Kurdzhieva; M. M. Shamuilova; E. M. Ledeneva (Лечащий Врач)
Background. In the article, a clinical case of managing a comorbid 74-year-old patient with a history ofischemic heart disease, who was hospitalized in a vascular center due to myocardial infarction, with subsequently developed acute kidney injury against the background of chronic kidney disease is presented.Objective. The purpose of describing this clinical case is to demonstrate the importance of assessing and considering the significance and modifiability of risk factors for the development of chronic kidney disease, as well as their timely correction. The clinical example illustrates the connection between impaired kidney function and the progression of cardiovascular pathology.Results. The patient described in the clinical case, despite a long history of hypertension, did not receive ambulatory combined antihypertensive therapy in accordance with actual clinical recommendations, but received a monopreparation from the class of angiotensin-converting enzyme inhibitors without achieving the target blood pressure. In 2012, the patient underwent coronary artery stenting due to unstable angina, after which she received only angiotensin-converting enzyme inhibitors and beta-blockers from the drugs recommended by clinicalguidelines and did not receive antithrombotic and lipid-lowering therapy. The patient was diagnosed with type 2 diabetes mellitus 20 years ago without subsequent control of glucose levels and choice of hypoglycemic therapy. In addition, the patient had modifiable risk factors of cardiovascular diseases and chronic kidney disease: long smoking history, obesity. Upon admission to the hospital, coronary angiography was performed with intravenous administration of iodine-containing contrast medium, according to the results of which stenosis of the right coronary artery was detected, and its stenting was performed with drug-coated stents. During the hospitalization period, there was an increase in the level of creatinine and urea in the blood serum with maximum values of 570.7 μmol/L and 37.1 mmol/L respectively. When these changes were detected, the patient was consulted twice by a nephrologist, and a decision was made to conduct sessions of replacement kidney therapy due to severe azotemia with persistent restoration of kidney function. Upon stabilization of the patient’s condition, she was discharged from the hospital with recommendations to continue the program hemodialysis. However, even upon admission to the hospital, the patient’s creatinine level was 260 μmol/L, which may indicate that chronic kidney disease had been developing for a long time before myocardial infarction and before the administration of X-ray contrast medium during coronary angiography.Conclusion. Thus, due to the management of the patient at the outpatient stage without compliance with clinical recommendations, lack of correction of modifiable risk factors for chronic kidney disease and cardiovascular pathology, it was not possible to prevent acute kidney injury against the background of chronic kidney disease and myocardial infarction due to late diagnosis of chronic kidney disease.